Isolation and Analysis of Chemical Components of Essential Oil of Baru Cina (Artemisia vulgaris L) Leaves and Antioxidant Activities Test - Ginting, Adil (Journal of Chemical Natural Resources, 2021)
Essential oil of Baru Cina leaves (Artemisia vulgaris L.) has been successfully isolated by hydrodistillation method using the Stahl apparatus. Baru Cina leaves were hydrodistillation for Â± 6 hours to produce the essential oil amount of 0.39 % (v/b). The essential oil obtained from Baru Cina leaves was characterized by using GC-MS spectroscopy. The GC-MS analysis results showed that there were 29 compounds and the main compounds identified as many as 14 compounds, such as Alpha-Pinene (0.33%), 1,8-Cineol (1.96% ), Filifoline (1.41 %), 1-Octen-3-Ol (2.99 %), 2,4-Cycloheptadien-1-0ne (Eucarvone) (30.61 %), 2-Cyclohexen-1-Ol (Cis) (2.86 %), Bicyclo-3,3,1-Hepta-3-One (1.62 %), Trans-Caryophyllene (4.82 %), 3-Cyclohexen-1-Ol (1, 71 %), 2-Cyclohexen-1-Ol(Trans) (2.75 %), 2-Cyclohexen-1-One (Piperitone) (30.92 %), Trans Carveol (0.31%), Ar-Dimethylphenethyl Alcohol (0.88%), Eugenol (2.42%). This study also showed antioxidant activity from the essential oil of Baru Cina leaves with the IC50 value was 95.76 mg/L.